Penerapan Prinsip Kehati-Hatiian Bagi Pejabat Notaris Dalam Membuat Akta Perjanjian Pengikatan Jual Beli Tanah Di Luar Wilayah Kerjanya (Indonesian Journal of Criminal Law, 2022)
The research objective to analyze the Notary Officer in applying the precautionary principle in making the Land Sale and Purchase Binding Agreement Deed outside his working area (2) to know and analyze the legal implications of the Notary's responsibility who does not apply the precautionary principle in making the Land Purchase Binding Agreement Deed outside work area. The theoretical and practical benefits of this research are expected to add to the knowledge of notarial law, especially strengthening the precautionary principle in making the deed of binding sale and purchase of land. This type of research is a normative legal research type. The results of the study (1) the application of the principle of prudence absolutely must be done to achieve legal certainty in order to protect the parties in the deed of agreement to bind the sale and purchase of land, and (2) the notary's responsibility is the implication of violating the norms that have been determined in the legislation. -laws, as well as the need for strengthening in order to prevent repeated violations of norms. Tujuan penelitian menganalisis Pejabat Notaris dalam menerapkan prinsip kehati-hatian dalam membuat Akta Perjanjian Pengikatan Jual Beli Tanah di luar wilayah kerjanya (2) mengetahui dan menganalisis implikasi hukum pertanggungjawaban Notaris yang tidak menerapkan prinsip kehati-hatiann dalam membuat Akta Perjanjian Pengikatan Jual Beli Tanah di luar wilayah kerjanya. Manfaat penelitian ini secara teoritis dan praktis diharapkan dapat menambah khasahan pengetahun hukum kenotariatan khususnya penguatan prinsip kehati-hatian dalam pembuatan akta perjanjian pengikatan jual beli tanah. Tipe penelitian ini merupakan tipe penelitian hukum normatif. Hasil penelitian (1) penerapan prinsip kehati-hatian mutlak harus dilakukan untuk mencapai kepastian hukum guna melindungi pihak-pihak yang ada di dalam akta perjanjian pengikatan jual beli tanah, dan (2) pertanggungjawaban notaris merupakan implikasi dari pelanggaran terahadap norma yang telah ditentukan dalam perundang-undangan, serta perlunya penguatan guna mencegah terjadinya pelanggaran norma secara berulang.